A General Numerical Method for Solving Riemann Problems (Journal of Computational Mathematics, 2021)
In this paper a general numerical method for solving Riemann problems is discussed. It can be used to solve the Riemann problems of various hyperbolic systems of differential equations with two independent variables. The problem of reflection of discontinuities from external boundaries can also be solved by this general numerical method.